Sintering process of surface modified short carbon fiber reinforced ceramic matrix composite material
Through the sintering process of surface-modified chopped carbon fiber and ceramic matrix material, the problem of brittle fracture of traditional ceramic materials in high stress environments is solved, the interface bonding strength and material properties are significantly improved, and it is suitable for applications in high temperature and harsh environments.
Patent Information
- Application Number
- CN202411451121.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-14
AI Technical Summary
Traditional ceramic materials are prone to brittle fracture under high stress environments, and the interface bonding strength between carbon fiber and ceramic matrix is insufficient, which affects the strengthening effect of composite materials.
The sintering process of surface-modified chopped carbon fiber and ceramic matrix material is adopted, including oxidation treatment of chopped carbon fiber and surface modification of coupling agent, and then uniformly mixed with ceramic powder, ensuring uniform mixing through ultrasonic dispersion or mechanical stirring, using cold etc. Static pressing or compression molding, and finally sintering in an inert atmosphere or vacuum environment.
It significantly improves the interface bonding strength between carbon fiber and ceramic matrix, improves the flexural strength, fracture toughness and impact resistance of composite materials, ensuring that the material maintains excellent mechanical properties and structural stability under high temperatures and harsh conditions.
Smart Images

Figure CN119306478A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon fiber reinforced ceramic matrix composite materials, in particular to a sintering process of a surface modified chopped carbon fiber reinforced ceramic matrix composite material. Background Art
[0002] In the research and application of ceramic matrix composites, ceramic materials are widely used in aerospace, automobile manufacturing, energy equipment and electronic components due to their excellent high hardness, high wear resistance and high temperature stability. However, traditional ceramic materials have low fracture toughness and impact resistance, and are prone to brittle fracture under high stress environments, which limits their application in complex working conditions. Therefore, how to effectively improve the toughness and overall mechanical properties of ceramic materials has become a key issue in the current research of ceramic matrix composites.
[0003] In recent years, carbon fiber reinforced ceramic matrix composites have gradually attracted attention due to their excellent mechanical properties and heat resistance. Carbon fiber has high strength, low density, good thermal stability and excellent fracture toughness, which can effectively improve the overall performance of ceramic matrix materials. However, due to the large interface difference between carbon fiber and ceramic matrix materials, especially during high-temperature sintering, carbon fiber is prone to oxidative decomposition, resulting in insufficient interface bonding strength, which in turn affects the reinforcement effect of the composite material.
[0004] In the prior art, some studies have improved the interfacial bonding performance between the fiber and the ceramic matrix by modifying the surface of the carbon fiber. For example, the carbon fiber is oxidized by an oxidant to increase the active groups on the fiber surface, or a coupling agent is used to form a chemical bonding layer on the fiber surface. However, these processes still have room for optimization in improving the interfacial bonding strength and material properties. In addition, chopped carbon fiber is widely used in the research of ceramic-based composites as a reinforcing phase because of its good dispersibility and low preparation cost, but how to achieve uniform dispersion of carbon fiber and avoid fiber agglomeration is still an important challenge in material preparation. Summary of the invention
[0005] The purpose of the present invention is to solve the technical problems raised in the above background technology.
[0006] The present invention adopts the following technical solution: a sintering process of a surface-modified chopped carbon fiber reinforced ceramic matrix composite material, comprising the following steps:
[0007] S1: Surface modification of chopped carbon fibers: The chopped carbon fibers are immersed in an oxidant solution for oxidation treatment, and then immersed in a solution containing a coupling agent. The modified chopped carbon fibers have a higher affinity and activity on the surface;
[0008] S2: Preparation of ceramic matrix material: The ceramic matrix material is selected to be alumina, silicon carbide, silicon nitride, etc., and the ceramic powder is prepared into a uniform powder by ball milling;
[0009] S3: Mixing chopped carbon fiber and ceramic powder: Mix the modified chopped carbon fiber and ceramic powder in a certain proportion, and use ultrasonic dispersion or mechanical stirring to make the two fully and evenly mixed;
[0010] S4: Compression molding: The mixed material is subjected to cold isostatic pressing or compression molding to obtain a primary body of the ceramic matrix composite material;
[0011] S5: Sintering: The formed green body is placed in a sintering furnace and sintered in an inert atmosphere or vacuum environment by a pressureless sintering or hot pressing sintering process to densify the composite material and obtain a surface-modified chopped carbon fiber reinforced ceramic matrix composite material.
[0012] Preferably, the oxidant for the surface modification treatment in S1 is at least one of nitric acid, sulfuric acid, and hydrogen peroxide, and the oxidation treatment time is 1 to 3 hours. Here, the use of oxidants such as nitric acid, sulfuric acid, or hydrogen peroxide to oxidize the chopped carbon fibers helps to improve the activity of the carbon fiber surface, form oxygen-containing functional groups on the surface, increase the bonding ability with the ceramic matrix, and improve the interface bonding strength, thereby enhancing the overall mechanical properties of the composite material, especially the flexural strength and fracture toughness.
[0013] Preferably, the coupling agent in S1 is at least one of a silane coupling agent, a titanate coupling agent or a zirconate coupling agent, and the immersion time is 0.5 to 2 hours. Here, the silane coupling agent, the titanate coupling agent or the zirconate coupling agent can form a chemically bonded interface layer on the surface of the chopped carbon fiber, thereby improving the interfacial adhesion between the carbon fiber and the ceramic matrix, and can further prevent the carbon fiber from being oxidized during the sintering process, thereby improving the heat resistance and anti-aging properties of the composite material.
[0014] Preferably, the particle size of the ceramic powder in S2 is 0.1 to 1 micron, and the ball milling time is 4 to 10 hours, and the ball-to-material ratio is 2: 1 to 5: 1. Here, the particle size of the ceramic powder is controlled within the range of 0.1 to 1 micron, and sufficient ball milling is performed to help improve the densification of the ceramic matrix, reduce the porosity in the material, and improve the mechanical properties of the material, such as hardness, density and fracture toughness. In addition, the uniform particle distribution can ensure the uniform distribution of carbon fibers and avoid performance inhomogeneity.
[0015] Preferably, the amount of chopped carbon fiber added in S3 accounts for 2% to 10% of the total mass of the ceramic powder, preferably 5%. Here, the amount of chopped carbon fiber added to the ceramic matrix is controlled to be 2% to 10%, which can greatly improve the toughness, impact resistance and heat resistance of the composite material without significantly increasing the weight of the material. When the amount is preferably 5%, the fracture toughness and impact absorption capacity of the material can be further improved while maintaining the high hardness of the material, making the composite material more suitable for use in harsh environments such as high temperature and strong impact.
[0016] Preferably, the cold isostatic pressing pressure in S4 is 100 to 300 MPa, the molding pressure is 10 to 50 MPa, and the pressing time is 5 to 30 minutes. Here, the cold isostatic pressing and molding use an isostatic pressing of 100 to 300 MPa and a molding pressure of 10 to 50 MPa, which helps to improve the density of the green body. Isostatic pressing can effectively reduce the pores generated during the molding process and make the green body more uniform, while molding provides better geometric accuracy and surface finish.
[0017] Preferably, the sintering temperature in S5 is 1200°C to 1600°C, preferably 1300°C to 1500°C, and the sintering holding time is 1 to 4 hours. Here, controlling the sintering temperature to 1200°C to 1600°C, preferably 1300°C to 1500°C, can effectively promote the crystal growth and densification of the ceramic matrix, while avoiding oxidation damage of the carbon fiber at too high a temperature, ensuring that the composite material has high hardness and heat resistance, while ensuring the structural integrity of the carbon fiber.
[0018] Preferably, the sintering environment in S5 is an inert gas environment such as nitrogen, argon or helium, or is carried out under vacuum conditions. Here, the oxidative decomposition of the carbon fiber during the sintering process can be effectively prevented, and the inert atmosphere can also improve the sintering behavior of the ceramic matrix and reduce the growth rate of the grains, thereby maintaining the high density and strength of the material. The vacuum environment further improves the purity of the material, making the composite material have better corrosion resistance and high temperature stability.
[0019] Preferably, in S5, the primary green body is degreased before sintering, and the degreasing treatment is performed at a temperature of 400°C to 600°C to remove the binder or other organic matter used in the molding process. Here, removing the binder or other organic matter in the green body before sintering helps to avoid pores or structural defects caused by organic residues during the sintering process. By performing degreasing at a temperature range of 400°C to 600°C, the purity of the green body can be ensured without destroying the green body, thereby improving the density and overall performance of the final composite material.
[0020] Compared with the prior art, the advantages and positive effects of the present invention are:
[0021] 1. In the present invention, the process is not only applicable to various ceramic matrices such as alumina, silicon carbide, silicon nitride, and zirconium oxide, but also can flexibly adjust process parameters such as oxidant type, coupling agent treatment time, ceramic powder particle size, molding pressure, and sintering temperature, thereby realizing customized preparation for different application requirements. The prepared composite material has extremely high toughness, wear resistance, and high temperature resistance, showing a wide range of application prospects.
[0022] 2. In the present invention, the interfacial bonding strength between the carbon fiber and the ceramic matrix is greatly enhanced by subjecting the chopped carbon fibers to oxidation treatment and surface modification with a coupling agent, and the flexural strength, fracture toughness and impact resistance of the composite material are significantly improved. Ultrasonic dispersion or mechanical stirring technology is used to ensure uniform mixing of the carbon fiber and ceramic powder. Combined with cold isostatic pressing or compression molding, the material is highly densified during the sintering process, the porosity is reduced, and the hardness and wear resistance of the material are further improved. By sintering in an inert gas or vacuum environment, the oxidative decomposition of the carbon fiber at high temperature can be effectively inhibited, ensuring that the composite material maintains excellent mechanical properties and structural stability under high temperature and harsh conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The present invention provides a flow chart of a sintering process for a surface-modified chopped carbon fiber reinforced ceramic matrix composite material. DETAILED DESCRIPTION
[0024] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0025] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.
[0026] Embodiment 1
[0027] See also Figure 1 The present invention provides a technical solution: a sintering process of a surface-modified chopped carbon fiber reinforced ceramic matrix composite material, comprising the following steps:
[0028] S1: Surface modification of chopped carbon fibers: The chopped carbon fibers are immersed in an oxidant solution for oxidation treatment, and then immersed in a solution containing a coupling agent. The modified chopped carbon fibers have a higher affinity and activity on the surface;
[0029] S2: Preparation of ceramic matrix material: The ceramic matrix material is selected to be alumina, silicon carbide, silicon nitride, etc., and the ceramic powder is prepared into a uniform powder by ball milling;
[0030] S3: Mixing chopped carbon fiber and ceramic powder: Mix the modified chopped carbon fiber and ceramic powder in a certain proportion, and use ultrasonic dispersion or mechanical stirring to make the two fully and evenly mixed;
[0031] S4: Compression molding: The mixed material is subjected to cold isostatic pressing or compression molding to obtain a primary body of the ceramic matrix composite material;
[0032] S5: Sintering: The formed green body is placed in a sintering furnace and sintered in an inert atmosphere or vacuum environment by a pressureless sintering or hot pressing sintering process to densify the composite material and obtain a surface-modified chopped carbon fiber reinforced ceramic matrix composite material.
[0033] In this embodiment, the oxidant used in the surface modification treatment in S1 is at least one of nitric acid, sulfuric acid, and hydrogen peroxide, and the oxidation treatment time is 1 to 3 hours.
[0034] Specifically, oxidation treatment of chopped carbon fibers with oxidants such as nitric acid, sulfuric acid or hydrogen peroxide helps to increase the activity of the carbon fiber surface, form oxygen-containing functional groups on the surface, increase the bonding ability with the ceramic matrix, improve the interface bonding strength, and thus enhance the overall mechanical properties of the composite material, especially the flexural strength and fracture toughness.
[0035] In this embodiment, the coupling agent is at least one of a silane coupling agent, a titanate coupling agent or a zirconate coupling agent, and the immersion time is 0.5 to 2 hours.
[0036] Specifically, the silane coupling agent, titanate coupling agent or zirconate coupling agent can form a chemically bonded interface layer on the surface of the chopped carbon fiber, thereby improving the interfacial adhesion between the carbon fiber and the ceramic matrix, and can further prevent the carbon fiber from being oxidized during the sintering process, thereby improving the heat resistance and anti-aging properties of the composite material.
[0037] In this embodiment, the particle size of the ceramic powder is 0.1 to 1 micrometer, the ball milling time is 4 to 10 hours, and the ball-to-material ratio is 2:1 to 5:1.
[0038] Specifically, the particle size of the ceramic powder particles is controlled within the range of 0.1 to 1 micron, and sufficient ball milling mixing is performed, which helps to improve the densification of the ceramic matrix, reduce the porosity in the material, and improve the mechanical properties of the material, such as hardness, density and fracture toughness. In addition, uniform particle distribution can ensure uniform distribution of carbon fibers and avoid performance inhomogeneity.
[0039] In this embodiment, the amount of chopped carbon fibers added is 2% to 10% of the total mass of the ceramic powder, preferably 5%.
[0040] Specifically, controlling the addition amount of chopped carbon fibers in the ceramic matrix to be 2% to 10% can greatly improve the toughness, impact resistance and heat resistance of the composite material without significantly increasing the weight of the material. When the addition amount is preferably 5%, the fracture toughness and impact absorption capacity of the material can be further improved while maintaining its high hardness, making the composite material more suitable for use in harsh environments such as high temperature and strong impact.
[0041] In this embodiment, the cold isostatic pressing pressure is 100 to 300 MPa, the molding pressure is 10 to 50 MPa, and the pressing time is 5 to 30 minutes.
[0042] Specifically, cold isostatic pressing and molding use an isostatic pressing pressure of 100 to 300 MPa and a molding pressure of 10 to 50 MPa, which helps to improve the density of the green body. Isostatic pressing can effectively reduce the pores generated during the molding process and make the green body more uniform, while molding provides better geometric accuracy and surface finish.
[0043] In this embodiment, the sintering temperature is 1200° C. to 1600° C., preferably 1300° C. to 1500° C., and the sintering holding time is 1 to 4 hours.
[0044] Specifically, controlling the sintering temperature to 1200°C to 1600°C, preferably 1300°C to 1500°C, can effectively promote the crystal growth and densification of the ceramic matrix, while avoiding oxidation damage to the carbon fiber at excessively high temperatures, ensuring that the composite material has high hardness and heat resistance, while ensuring the structural integrity of the carbon fiber.
[0045] In this embodiment, the sintering environment is an inert gas environment such as nitrogen, argon or helium, or is performed under vacuum conditions.
[0046] Specifically, an inert gas environment such as nitrogen, argon, helium, or vacuum sintering can effectively prevent the oxidative decomposition of carbon fibers during the sintering process. The inert atmosphere can also improve the sintering behavior of the ceramic matrix and reduce the growth rate of the grains, thereby maintaining the high density and strength of the material. The vacuum environment further improves the purity of the material, giving the composite material better corrosion resistance and high-temperature stability.
[0047] In this embodiment, the preform is degreased before sintering. The degreasing process is performed at a temperature of 400° C. to 600° C. to remove a binder or other organic matter used in the molding process.
[0048] Specifically, removing the binder or other organic matter in the green body before sintering helps to avoid porosity or structural defects caused by organic residues during the sintering process. By debinding at a temperature range of 400°C to 600°C, the internal purity of the green body can be ensured without destroying it, thereby improving the density and overall performance of the final composite material.
[0049] Embodiment 2
[0050] In this embodiment, the ceramic matrix material is alumina, and the mass fraction of the chopped carbon fibers is 5%.
[0051] S1: The chopped carbon fiber is immersed in a 20% by mass nitric acid solution for oxidation treatment for 2 hours, and then the carbon fiber is immersed in a 5% by mass silane coupling agent solution for 1 hour to improve the surface activity of the carbon fiber;
[0052] S2: The particle size of the aluminum oxide powder is controlled at 0.5 μm, and the powder is ball-milled in a ball mill for 6 hours with a ball-to-material ratio of 3:1 to obtain uniform aluminum oxide powder;
[0053] S3: The modified chopped carbon fiber and alumina powder are mixed at a ratio of 5%, and the two are evenly distributed using ultrasonic dispersion technology;
[0054] S4: placing the mixed material into a mold and performing cold isostatic pressing to form the mixed material. The isostatic pressing pressure is 200 MPa and the pressing time is 15 minutes to obtain a primary body.
[0055] S5: placing the green body into a sintering furnace in an argon protective atmosphere, setting the temperature to 1400° C., and keeping the temperature for 2 hours, and obtaining a densified alumina-based chopped carbon fiber reinforced ceramic composite material after cooling.
[0056] Embodiment 3
[0057] This embodiment uses silicon carbide as the matrix material, and the mass fraction of the chopped carbon fibers is 3%.
[0058] S1: The chopped carbon fiber was oxidized in a 20% sulfuric acid solution for 1 hour, and then immersed in a titanate coupling agent solution for 0.5 hour. After surface modification, the surface bonding ability of the carbon fiber was enhanced;
[0059] S2: The particle size of silicon carbide powder is 0.3 μm, and it is ball milled for 8 hours with a ball-to-material ratio of 4:1;
[0060] S3: 3% chopped carbon fiber is uniformly mixed with silicon carbide powder and further uniformly distributed by mechanical stirring and ultrasonic dispersion;
[0061] S4: Molding is performed by compression molding, the compression pressure is 30 MPa, and the compression time is 20 minutes;
[0062] S5: In a vacuum environment, the sintering temperature is 1500°C, the holding time is 3 hours, and after cooling, a densified silicon carbide-based chopped carbon fiber reinforced ceramic composite material is obtained.
[0063] Embodiment 4
[0064] In this embodiment, silicon nitride is selected as the matrix material, and the mass fraction of the chopped carbon fibers is 7%.
[0065] S1: The chopped carbon fibers were treated with a 30% by mass hydrogen peroxide solution for 1 hour, and then immersed in a zirconate coupling agent solution for 2 hours. The modified fiber surface was more active.
[0066] S2: The particle size of silicon nitride powder is 0.8 μm, the ball milling time is 10 hours, the ball-to-material ratio is 5:1, and a uniform powder is prepared;
[0067] S3: Mix 7% chopped carbon fiber with silicon nitride powder, and use mechanical stirring to ensure that the two are evenly dispersed;
[0068] S4: cold isostatic pressing is used for molding, the isostatic pressing pressure is 250 MPa, and the pressing time is 10 minutes;
[0069] S5: In a nitrogen protective atmosphere, the sintering temperature is 1350°C, the holding time is 4 hours, and after cooling, a dense silicon nitride-based chopped carbon fiber reinforced ceramic composite material is obtained.
[0070] Embodiment 5
[0071] In this embodiment, the ceramic matrix material is zirconium oxide, and the mass fraction of the chopped carbon fibers is 6%.
[0072] S1: Put the chopped carbon fiber into a hydrogen peroxide solution (concentration of 15%) for oxidation treatment for 1.5 hours. After the oxidation treatment, soak the carbon fiber in a silane coupling agent solution with a mass fraction of 3% for 1 hour to ensure that a chemically active layer is formed on the surface of the carbon fiber to enhance its bonding ability with the zirconium oxide matrix;
[0073] S2: The particle size of the zirconium oxide powder is controlled at 0.2 μm, and the powder is ball milled for 6 hours with a ball-to-material ratio of 3:1 to obtain uniform zirconium oxide powder;
[0074] S3: 6% surface-modified chopped carbon fibers are mixed with zirconium oxide powder in proportion, and the two are further dispersed uniformly by mechanical stirring and ultrasonic dispersion technology, so that the carbon fibers are evenly distributed in the zirconium oxide matrix;
[0075] S4: placing the mixed material in a mold and forming it by cold isostatic pressing, with the isostatic pressing pressure set to 150 MPa and the pressing time being 12 minutes to obtain a dense primary body;
[0076] S5: placing the green body into a sintering furnace in an argon protective atmosphere, setting the sintering temperature to 1450° C., holding time to 2.5 hours, and obtaining a dense zirconia-based chopped carbon fiber reinforced ceramic composite material after cooling.
[0077] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A sintering process for a surface-modified chopped carbon fiber reinforced ceramic matrix composite material, characterized in that: The following steps are involved: S1: Surface modification of chopped carbon fibers: The chopped carbon fibers are immersed in an oxidant solution for oxidation treatment, and then immersed in a solution containing a coupling agent. The modified chopped carbon fibers have a higher affinity and activity on the surface; S2: Preparation of ceramic matrix material: The ceramic matrix material is selected to be alumina, silicon carbide, silicon nitride, etc., and the ceramic powder is prepared into a uniform powder by ball milling; S3: Mixing chopped carbon fiber and ceramic powder: Mix the modified chopped carbon fiber and ceramic powder in a certain proportion, and use ultrasonic dispersion or mechanical stirring to make the two fully and evenly mixed; S4: Compression molding: The mixed material is subjected to cold isostatic pressing or compression molding to obtain a primary body of the ceramic matrix composite material; S5: Sintering: The formed green body is placed in a sintering furnace and sintered in an inert atmosphere or vacuum environment by a pressureless sintering or hot pressing sintering process to densify the composite material and obtain a surface-modified chopped carbon fiber reinforced ceramic matrix composite material.
2. The sintering process of the surface modified chopped carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The oxidant used in the surface modification treatment in S1 is at least one of nitric acid, sulfuric acid and hydrogen peroxide, and the oxidation treatment time is 1 to 3 hours.
3. The sintering process of the surface modified chopped carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The coupling agent in S1 is at least one of a silane coupling agent, a titanate coupling agent or a zirconate coupling agent, and the immersion time is 0.5 to 2 hours.
4. The sintering process of the surface modified chopped carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The particle size of the ceramic powder in S2 is 0.1 to 1 micron, the ball milling time is 4 to 10 hours, and the ball-to-material ratio is 2:1 to 5:
1.
5. The sintering process of the surface modified chopped carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The amount of the chopped carbon fibers added in S3 is 2% to 10% of the total mass of the ceramic powder, preferably 5%.
6. The sintering process of the surface modified chopped carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The cold isostatic pressing pressure in S4 is 100 to 300 MPa, the molding pressure is 10 to 50 MPa, and the pressing time is 5 to 30 minutes.
7. The sintering process of the surface modified chopped carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: In the step S5, the sintering temperature is 1200° C. to 1600° C., preferably 1300° C. to 1500° C., and the sintering holding time is 1 to 4 hours.
8. The sintering process of the surface modified chopped carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The sintering environment in S5 is an inert gas environment such as nitrogen, argon or helium, or is carried out under vacuum conditions.
9. The sintering process of the surface modified chopped carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: In the step S5 , the primary body is subjected to a degreasing treatment before sintering. The degreasing treatment is performed at a temperature of 400° C. to 600° C. to remove a binder or other organic matter used in the molding process.
Citation Information
Patent Citations
Preparation method for short carbon fiber / silicon carbide composites
CN103204693A
Short fiber reinforced silicon carbide sealing ring ceramic part and preparation method thereof
CN104876615A
Fiber-toughened silicon carbide ceramic impeller and gel injection molding preparation method thereof
CN106946571A
Silicon nitride circuit substrate material and preparation method thereof
CN110395989A
Preparation method of modified carbon fiber / SiO2 aerogel composite material
CN113860848A
Cited By
Preparation method of high-performance silicon nitride ceramic
CN120518396A
Ceramic salt core for high-pressure casting of refrigerant runner plate
CN120551325A
Ceramic salt core for high pressure casting of coolant runner plate
CN120551325B
Carbon fiber reinforced alumina-based composite armor material
CN120887730A
Lightweight injection molding part and preparation method thereof
CN121021976A